Os impactos sociais provocados pela atividade mineradora no município de Juruti - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The large mineral projects implemented in Brazil, especially in the Amazon, have dynamics marked by impacts, whether social, economic or environmental. This research deals with the social impacts generated by the Bauxite Extraction Project by the multinational Aluminum Company of America - ALCOA, in the municipality of Juruti (PA). The methodology is based on analysis of graphics, as well as dialogues with authors who in previous moments have already refuted on the subject. We highlight some impacts that a priori we consider important, such as GDP, education, health, etc. The objective of this work is to identify the main social impacts arising from the arrival of the mining company Alcoa in the Municipality of Juruti/PA. The present study emphasizes the transformations that took place from the first decade of the 21st century onwards and the unfolding of the existing relationships between the mining activity and the changes that occurred in the municipality from the implementation of the project.
Keywords: Mineração de bauxita; Impactos sociais; Juruti; ALCOA; CNPQ:: CIÊNCIAS EXATAS